İnşaat şirketlerinde riskin algılanması ve risk azaltıcı tedbirler - Şener, Bahar (My University, 2012)
Risk denilen olgu sadece inşaat sektöründe değil tüm sektörlerde yer alır ve her sektörde önemli bir yere sahiptir. Fakat inşaat sektöründe riskin önemi diğer birçok sektörden çok daha fazladır. Çalışma içerisinde bu önemin nedenleri üzerinde durulmaktadır. Risk yönetimi kavramı inşaat sektöründe uzun yıllardan beridir var olmadığından, Türkiye'de inşaat sektöründeki firmalar da risk yönetimiyle ilgili yeteri kadar bilgi sahibi değiller. Bu çalışmada inşaat firmalarının risk yönetimi konusunda yeterli deneyime sahip olmadığı, fakat yavaş da olsa zaman içerinde bu bilincin arttığı kanıtlanmıştır. İnşaat sektörü içerisinde firmalar birçok riske maruz kalmaktadırlar ve bu riskleri bertaraf etmek ve/veya en aza indirmek için pek çok risk araç ve yöntemleri kullanılmaktadır. Bu çalışmanın amacı da bir anket çalışmasıyla Türkiye'deki müteahhit firmalarının risk yönetiminin kullanımının araştırılmasıdır.

The risk is a fact that which appears in every industrial sector but not just construction industry and it has been given so much attention by each industrial sector. However the importance of the risk in construction industry is so much powerful than its importance for any other industry. The reasons of that importance of the risk in construction industry are being detailed in the study. Since the history of concept of risk management in construciton industry has not been existed for a long time, the companies in the Turkish construction industry haven?t been aware of the risk management as they should have been. In this study, it has been proved that the companies in the Turkish construction industry do not have the enough experience in risk management but meanwhile in time the consciousness about the risk management is continuously increasing. In the construction industry the companies are being exposed to countless risks on the other hand there are so many risk management tools that are being used to eliminate or minimize the effects of those risks. The aim of this study is to investigate the usage of risk manegement by companies in the Turkish construction company via a survey.
Perception of the risk for construction companies and the risk reducing precautions
Keywords: inşaat mühendisliği; civil engineering; müteahhitler; constractors; risk yönetimi; risk management; inşaat; construction